PERJANJIAN JUAL BELI BAHAN BAKAR MINYAK JENIS HIGH SPEED DIESEL ANTARA PT. PRAYASA INDOMITRA SARANA DENGAN PT. BUMA NIAGA PERKASA - RADEN DIAN NUGROHO KUSUMA (PREMISE LAW JURNAL, 2013)
ABSTRACT In general, the oil trading agreement has met the requirements of agreement validity, but to have its legal capacity, the parties involved must have legal authority. The validity of trading agreement also depends on the agreement between the goods and its price, commencing from the delay of goods price agreement to the fulfillment of the event agreed, and it does not mean that the agreement is delayed besides the delay of the power of legal engagement in the agreement. The contractual responsibility of the parties involved is based on contractual bound and the norms of trading agreement as good agreement. Contractual responsibility commences from failing to meet what agreed in the agreement that is realized in the forms of paying the expenditures, compensation and expected profit. The responsibility of the parties involved commences because the business permit of the seller is revoked, not due to legal committment in the agreement but based on onrechtmatigedaad.. In relation to the equilibrium principle, values of equiblirium balance are seen through the principal achievement of trading agreement, but if an unbalanced norms of agreement appears afterwards, the norms in proportional balance will take over the role to consider whether or not the unbalanced values occur or there are proportional equilibrium values instead. Keywords: Trading Agreement, Fuel of Oil, Contractual Responsibility, In-Agreement Balance PrincipleABSTRACT In general, the oil trading agreement has met the requirements of agreement validity, but to have its legal capacity, the parties involved must have legal authority. The validity of trading agreement also depends on the agreement between the goods and its price, commencing from the delay of goods price agreement to the fulfillment of the event agreed, and it does not mean that the agreement is delayed besides the delay of the power of legal engagement in the agreement. The contractual responsibility of the parties involved is based on contractual bound and the norms of trading agreement as good agreement. Contractual responsibility commences from failing to meet what agreed in the agreement that is realized in the forms of paying the expenditures, compensation and expected profit. The responsibility of the parties involved commences because the business permit of the seller is revoked, not due to legal committment in the agreement but based on onrechtmatigedaad.. In relation to the equilibrium principle, values of equiblirium balance are seen through the principal achievement of trading agreement, but if an unbalanced norms of agreement appears afterwards, the norms in proportional balance will take over the role to consider whether or not the unbalanced values occur or there are proportional equilibrium values instead. Keywords: Trading Agreement, Fuel of Oil, Contractual Responsibility, In-Agreement Balance Principle